The Role of Big Data Analytics in Determine the Relationship between Green Product Innovation, Market Demand and the Performance of Motorcycle Manufacturing Firms in Thailand - Saroge Vasuvanich; Sudawan Somjai; Komkrit Rattamanee; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2020)
The study is carried out to explore the role of big data analytics in determine the relationship between green product innovation, market demand and the performance of motorcycle manufacturing firms in Thailand. The current study which basically is an empirical research theoretically as well as methodologically contributed in the existing literature, particularly, in the Thailand’s motorcycle industry. It is obvious that adopting green product innovation in highly competitive market is imperative, since it facilitates in achieving competitive advantage and product differentiation [1].the data is collected from the motorcycle manufacturing firms in Thailand. The SEM-PLS is used to analyse the data. The findings of the study have shown consistency with the hypothesized results as well as the prior findings. Although, the results have shown that it is important for firms to understand the requirements of its consumers, followed by the alignment of product innovation initiatives to the values of consumers. In the recent green conscious competitive environment, brand identity and design, price, fuel consumption, and exhaust emission are some of the important criteria which are generally considered by consumers while taking a motorbike purchasing decision. Another study has attempted to analyse BDA and the computer-assisted textual analysis, as well as its application in the transportation and logistics system. For the managers, the current research emphasizes the strategic significance of green product decisions. It also explains that firm performance and green product innovation must also integrate knowledge of market demand as important consideration.